Analysis of Green Intellectuals, Environmentally Friendly and Green Competitive Behaviors on the Advantages of Green Motivation at PT Dian Daya Dinamika - Wenny Desty Febrian; Yanthy Herawaty Purnama; Indra Sani (MultiTech Publisher, 2023)
In today's industrial world, the environment functions as a resource for the survival and sustainability of industrial activities themselves as well as a place to live or stand. Companies such as PT Dian Daya Dinamika, as well as the community and government, are paying attention and taking serious action on these environmental issues. Regarding the state of the environment and depleting of natural resources, the company has made a significant contribution. which got worse. Businesses should encourage green production in their operations, but a green environment does not necessarily require zero pollution. This research aims to examine the behavior of environmentally friendly employees towards green motivation. To achieve green competitive advantage (Y), manufacturing companies need green intellectual (X1) and environmentally friendly behavior (X2) in their operations as well as green motivation (X3). This research uses a literature review method. The output was submitted to an international journal, namely Copernicus